Increased electrical conductivity dispersion -hardened copper - F. G. Lovshenko; A. I. Khabibulin (Литьë и металлургия, 2020)
The material, obtained in reactor, is a composition, consisting of a copper matrix of microcrystalline type with the borders of grains, stabilized by disperse particles of strengthening phases in the size of less than 20 nanometers. It is established, that the application of oxide nitrogen N2O as the technological environment at mix material processing in reactor activates the oxidationreduction transformations, which take place in mechanically alloyed compositions on the basis of system Cu–Al–CuO–MoO3, that leads to decrease in concentration of aluminium in a copper-based solid solution and, as a consequence, increases electrical conductivity of the material by 14 %, reaching values of 80 % from electrical conductivity of copper. It is shown, that the developed material is characterized by high stability against long thermal influence at the temperatures, reaching 0, 85 of temperatures of a basis fusion, which is explained by its structure.